2017
DOI: 10.1371/journal.pone.0184755
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a highly specific polyclonal antibody against human extracellular signal-regulated kinase 8 and its detection in lung cancer

Abstract: Extracellular signal-regulated kinase 8 (ERK8), proposed as a novel potential therapeutic target for cancer, has been implicated in cell transformation, apoptosis, the protection of genomic integrity, and autophagy. To facilitate ERK8 research, a highly specific anti-ERK8 antibody is needed. In this article, we use the Immune Epitope Database and Analysis Resource online tool to predict B-cell epitopes of human ERK8 protein, and choose a 28 aa-peptide sequence to generate the GST-ERK8(28aa) fusion protein as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Apart from the intracellular environment of lung tumor cells influencing the relaxivity of GdCho-Len, detection of lung tumor cells was difficult to see on the imaging volume within which these cells were embedded (43)(44)(45). The present study indicated that the GdCho-Len allowed Len to discriminate between lung cancer cells, which enhanced the diagnostic sensitivity of PET/CT.…”
Section: Discussionmentioning
confidence: 67%
“…Apart from the intracellular environment of lung tumor cells influencing the relaxivity of GdCho-Len, detection of lung tumor cells was difficult to see on the imaging volume within which these cells were embedded (43)(44)(45). The present study indicated that the GdCho-Len allowed Len to discriminate between lung cancer cells, which enhanced the diagnostic sensitivity of PET/CT.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, MAPK15 overexpression may contribute to the malignant transformation of male germ cells by controlling a "stress support" autophagic pathway, which prevents DNA damage and the consequent activation of the tumor suppressor TP53 (Rossi et al, 2016). Our recent tissue array analysis also demonstrated that the MAPK15 protein was localized in both the nucleus and cytoplasm of human lung cancers (Cai et al, 2017 (Groehler & Lannigan, 2010). Previously, it has been shown that loss of MAPK15 was correlated with breast cancer progression, and all estrogen receptor (ESR) alpha-positive breast tumors had decreased MAPK15 expression compared with that found in normal breast tissue (Henrich et al, 2003).…”
Section: Mapk15 Protein Interactomementioning
confidence: 69%
“…Their results revealed that the raised rabbit-specific pAbs against human extracellular signal-regulated kinase 8 were able to perform as a sensitive antibody for cancer case studies. (36) Considering the WB analyzing, our generated camelid pAbs were able to detect recombinant CTLA-4 protein on the nitrocellulose membrane (Fig. 4).…”
Section: Discussionmentioning
confidence: 96%